Authentic Materials and Tasks as Mediators to Develop EFL Students' Intercultural Competence - Alix Norely Bernal Pinzón (Asociación Colombiana de Profesores de Ingles, 2020)
This article reports on a study carried out in a foreign language course at a private Colombian university. Its purpose was to identify the role of authentic materials and tasks, based on cultural topics, in the development of intercultural competence in third-level English students. The pedagogical implementation of the activities was designed under criteria proposed by Cortazzi and Jin (1999) to evaluate the material with cultural content. In regard to intercultural competence, Byram's (2002) dimension of intercultural communicative competence was the support for planning and implementing the tasks. In this qualitative action research study, two surveys, one interview, and teacher field notes were used to collect data. Findings indicate that students were able to understand interculturality, to show respect for other cultures, and to demonstrate interest in getting to know other societies. Likewise, the students reported their willingness to be open to discussing topics related to cultural aspects.